Impact of pull–push motivations on tourist satisfaction and loyalty: the moderating role of Islamic attributes in shaping destination image - Arif Jameel; Abid Hussain; Shahida Kanwel; Wenjing Guo; Sania Khan (Humanities & Social Sciences Communications)
Abstract The present research aims to examine the impact of travel motivation factors—namely push and pull motivations—alongside the Islamic destination image (IDI) on tourist satisfaction (TS) and destination loyalty (DL) while also exploring the moderating effect of Islamic Attributes (IA) within these relationships. Based on the push–pull motivation theory, the conceptual framework and hypotheses were established based on a complete study of the existing theoretical and empirical literature. Data were gathered by a standardized questionnaire distributed in the Kingdom of Saudi Arabia, resulting in 630 valid responses from a cross-sectional survey utilizing convenience sampling. Using SPSS and AMOS to evaluate the proposed relationships, structural equation modeling was used. The results indicate that both push and pull motivations substantially impact tourist satisfaction and influence the perception of the destination’s image. Additionally, the image of an Islamic destination positively correlates with satisfaction and loyalty, with Islamic attributes moderating various critical relationships. The findings emphasize the necessity for tourism stakeholders, including government agencies and private sector organizations, to prioritize elements such as religious motivation, cultural familiarity, halal-compliant amenities, Sharia-compliant services, and family-oriented environments. These factors are essential for improving visitor satisfaction and loyalty, establishing Saudi Arabia as a premier halal tourism destination for Muslim travelers worldwide.